Traditional and modern employee benefits in Myanmar's manufacturing sector - Henrik Hansen; John Rand; Neda Trifkovic (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Employer-provided benefits are independent elements in the compensation packages that make up firms' payment strategies. Such benefits are aimed at attracting and retaining preferred employees and improving incentives. In Myanmar, there are two employee benefit systems: (1) an unregulated traditional system in which firms offer their employees in-kind benefits such as meals and accommodation; and (2) a modern mandatory system in which firms are required by law to offer payment schemes such as payment-while-absent and compensation for accidents. Using a survey of matched employers and employees in the manufacturing sector in Myanmar, we identify firms and workers that supply and demand the two types of employee benefits. We show that traditional benefits are widely supplied and demanded, while modern benefits are supplied by fewer firms and provided to fewer workers. We analyse the relative importance of a range of observable firm and worker attributes that may be associated with the supply and demand for the benefits. We find that firms that provide accommodation appear to attract young, unmarried, uneducated workers who are often migrants, and who, on average, receive lower wages compared to similar workers who do not receive equal in-kind payments. Large firms are more likely to offer the modern benefits and highly educated workers are more likely to demand them. Moreover, workers who receive modern benefits tend to stay longer with the firm and the benefit appears not to have an adverse impact on their wage level. Our findings indicate that both types of benefits contribute to sorting in the labour market. Therefore, both must be considered when labour laws are amended. Moreover, if increased minimum wages are accompanied by reduced provision of traditional in-kind benefits to low-wage workers, then there is a real risk that inequality in consumption will increase even though wage inequality decreases.
Keywords: J33; K31; M52; O53; 330; compensation packages; employee benefits; labour law; Myanmar